A Comprehensive Systematic Review of The Relationship between Vitamin E Consumption and the Risk of Preeclampsia - Faizal Akbar Farid Musliem (International Medical Journal Corp. Ltd, 2026)
Background: Preeclampsia remains a leading cause of maternal and perinatal morbidity and mortality worldwide. Oxidative stress has been implicated in its pathogenesis, positioning vitamin E as a potential preventive agent due to its antioxidant properties. However, evidence regarding its efficacy remains conflicting. Methods: A comprehensive systematic review was conducted following PRISMA guidelines. We searched multiple databases for studies examining the relationship between vitamin E consumption and preeclampsia risk. Inclusion criteria encompassed randomized controlled trials, cohort studies, case-control studies, and cross-sectional studies involving pregnant women. Data extraction included study characteristics, vitamin E exposure details, preeclampsia outcomes, biochemical markers, and confounding variables. Forty-six studies met inclusion criteria, comprising 12 RCTs, 8 cohort studies, 15 case-control studies, 13 cross-sectional studies, and 2 reviews. Results: RCTs demonstrated heterogeneous findings. While one trial using tocotrienol-rich fraction showed 97% risk reduction (aOR 0.030, 95% CI: 0.001-0.65; Aminuddin et al., 2021), large trials found no benefit (Poston et al., 2006; Beazley et al., 2005). The largest cohort study (n=73,317) identified a threshold effect at 7.3 mg/L serum vitamin E, with levels <5.5 mg/L associated with 29.56-fold increased risk (Shi et al., 2022). Observational studies consistently demonstrated lower vitamin E levels in preeclamptic women (Chaudhary et al., 2022; Aamir et al., 2021; Nnamdi et al., 2021). Dietary intake studies showed low intake was associated with increased risk (Rumbold et al., 2005; Masrikhiyah et al., 2016), but supplementation >100 mg/day in replete women was associated with harm (OR 1.68; Yang et al., 2025). Biochemical studies confirmed elevated oxidative stress markers and reduced antioxidant capacity in preeclampsia (Omar et al., 2019; Suhail et al., 2008; Begum et al., 2012). Discussion: The apparent contradiction between RCTs and observational studies is reconciled by baseline vitamin E status. The threshold effect at 7.3 mg/L explains why supplementation benefits deficient populations but not replete populations. Form of vitamin E (tocotrienols vs. alpha-tocopherol) and dose considerations are critical. Conclusion: Routine vitamin E supplementation is not supported in well-nourished populations. Targeted supplementation in vitamin E-deficient women (serum <7.3 mg/L) warrants further investigation.